The relationship between levels of knowledge and interest in using the partial dentures: A case at Yogyakarta's private dental clinic, Indonesia - Haryani, Wiworo; Indahsari, Rachma; Sutrisno (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Missing or lost teeth after tooth extraction may lead to tooth decay and infection. Many cases of tooth loss will not be followed with prosthodontics or rehabilitative treatments. Patients might be aware of partial denture, however no concern to replace the missing teeth.Aims: This study was to determine the relationship between the levels of knowledge and interest in using the partial dentures.Methods: This study was an observational analytic survey with cross sectional design, conducted in October - November 2017. The work involved 60 patients who had pulled teeth at Kanina Dental Clinic, Yogyakarta, Indonesia, who had been selected using purposive sampling technique. Levels of knowledge and interest among the participants were assessed by a set of questionnaire. The data obtained was then analysed using Kendall's Tau test.Results: From the study, we found that 35 respondents had good knowledge and high interest to use partial dentures (58.3%), while the other 22 patients (40%) had been noted with less knowledge and poor maintenance. From Kendall's Tau test, we found a significant relationship between the patient's knowledge and partial removal denture maintenance of p value = 0.003. This study also highlights the role of patients' peer to their decision to use the removable partial dentures.Conclusion: Respondents may consider loosing teeth affected to their physical aesthetics, masticatory system, and speaking comfort. Data shows the higher knowledge to the benefits of partial dentures the higher their interest in using removable partial dentures after tooth extraction. Keywords: Knowledge, Interest, Use of partial dentures Received: 27 January 2018, Reviewed: 06 February 2018, Received in revised form: 24 February 2018, Accepted: 28 February 2018. DOI: https://doi.org/10.35898/ghmj-21191